The Effect of the Therapist’s Degree of Focus on Defense and His Level of Accurate Empathy on Therapeutic Outcome - Truax, Charles B.; Wittmer, Joe (Canadian Journal of Counselling and Psychotherapy, 2012)
No abstract available